PENGARUH KESADARAN WAJIB PAJAK, SANKSI PERPAJAKAN, PENGETAHUAN PERPAJAKAN, DAN PELAYANAN FISKUS - Teguh Erawati; Andrea Meylita Widyasti Parera (Jurnal Akuntansi, 2017)
This study aimed to examine the effect of awareness of taxpayers, tax penalties, tax knowledge, and service tax authorities on tax compliance and building earth. The sampling technique in this study using a convenience sampling (convenience sampling) to 110 taxpayer earth and office buildings in the Department of Revenue, Finance and Asset Management Area (DPPKAD) Yogyakarta that meet the criteria. The data used are primary data through questionnaires, which contain a respondent's answers. Analysis of the data in this study using descriptive analysis and multiple linear regression analysis. The first hypothesis: awareness taxpayer positive effect on tax compliance on land and buildings, both: tax penalty positive effect on tax compliance on land and buildings, three: knowledge of taxation positive effect on tax compliance on land and buildings, a fourth: the service tax authorities positive effect on tax compliance and building earth. The fourth hypothesis can be proved by the results of the study showed that awareness of taxpayers, tax penalties, tax knowledge, and service fiskus positive effect on tax compliance and building earth. Keywords: Awareness of taxpayers, tax penalties, tax knowledge, Service tax authorities, taxpayers Compliance